Does financial agglomeration contribute to the coordination of pollution and carbon reduction? Test analysis based on the threshold model and spatial Durbin model - Chen, Shanshan; Zeng, Shibo; Lai, Yinqiang; Bai, Yongliang (Frontiers in Environmental Science, 2026)
It is crucial for China to determine whether financial agglomeration can increase the degree of coordination between pollution and carbon reduction to expedite the achievement of full green economic transformation. This study, using the data of 283 cities in China from 2007 to 2021 as samples, innovatively explores the threshold effect and spatial effect of financial agglomeration (FA) on the coordination of pollution and carbon reduction (CPC) by constructing a panel threshold regression model and a spatial Durbin model. It also examines the spatial mechanism and regional heterogeneity of these two factors from a spatial perspective. The findings indicate the following: First, FA has a notable threshold effect on the CPC. The presence of threshold variables, such as government support, industrial structure, and financial development, results in the emergence of two distinct threshold effects. Conversely, when the threshold variable of FA is considered, only a single threshold effect is observed. And the threshold value of FA is 0.2972. Second, throughout the research period, both the degree of FA and the level of the CPC exhibit notable characteristics of positive spatial correlation. Third, the impact of FA on the CPC exhibits a nonlinear “U-shaped”characteristic in spatial terms, with government support and human capital serving as the underlying mechanisms. Fourth, the spatial impact of FA and its threshold effect vary by location. This study deeply explores the influence mechanism of FA on CPC, and puts forward policy suggestions relevant policy suggestions from the perspectives of government support, adjustment of industrial frameworks, and progress in the financial sector, which can provide policy references for enhancing the level of CPC of China.